Analysis of seismic supporting effects of bolt and lining of underground caverns. (June 2015) - Yang, Y.; Chen, J. T.; Xiao, M.
<x content-type="archive" xml:space="preserve">Abstract</x> Aiming at the issue of seismic strengthening of underground caverns, a strain rate-dependent plastic constitutive model is established. In addition, dynamic algorithms of bolt and lining are presented. Using the proposed model and algorithms, the influences of parameter variations of bolt and lining on seismic strengthening of underground caverns have been calculated. The results show that bolt and lining can effectively improve the seismic stability of underground caverns. Furthermore, supporting effects of bolt are superior to lining. The optimum support parameters of both bolt and lining support are existed. Below the optimum support parameters, with the improvement of parameters, the supporting effect is significantly enhanced. Above the optimum support parameters, the supporting effect will be slightly enhanced. The optimum support parameters vary at different positions of the caverns. The research provides a theoretical basis for seismic design of caverns.